2001
DOI: 10.1302/0301-620x.83b7.11654
|View full text |Cite
|
Sign up to set email alerts
|

Intraneural mucoid pseudocysts

Abstract: A mucoid pseudocyst of a peripheral nerve is a rare and benign tumour of controversial origin. We have reviewed ten patients with a mean follow-up of 3.2 years. The tumour affected the common peroneal nerve in eight and the ulnar nerve in two. The mean time between the onset of symptoms and diagnosis was 7.4 months (1.2 months to 2 years). On examination, there was pain in eight patients and swelling in seven. Motor deficit in the corresponding nerve territory was found in all. The diagnosis was usually confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
(16 reference statements)
0
20
0
2
Order By: Relevance
“…They most often affect the fibular (peroneal) nerve, arising there from the superior tibiofibular joint, but examples have been reported to involve the ulnar nerve at the elbow (Zum Busch, 1895;Jardini, 1907;Tanaka et al, 1969;Hori et al, 1986;Allieu et al, 1987;Hansis et al, 1988;Allieu and Cenac, 1989;Ferlic and Ries, 1990;Inhofe and Moneim, 1996;Harway, 1997;Uetani et al, 1998;Choi et al, 1999;Sharma et al, 2000;Chick et al, 2001;Chan et al, 2003;Rezzouk and Durandeau, 2004;Boursinos and Dimitriou, 2007;Lohmeyer et al, 2007). These latter cases in every way resemble the case reported herein.…”
Section: Scientific Clarificationmentioning
confidence: 99%
“…They most often affect the fibular (peroneal) nerve, arising there from the superior tibiofibular joint, but examples have been reported to involve the ulnar nerve at the elbow (Zum Busch, 1895;Jardini, 1907;Tanaka et al, 1969;Hori et al, 1986;Allieu et al, 1987;Hansis et al, 1988;Allieu and Cenac, 1989;Ferlic and Ries, 1990;Inhofe and Moneim, 1996;Harway, 1997;Uetani et al, 1998;Choi et al, 1999;Sharma et al, 2000;Chick et al, 2001;Chan et al, 2003;Rezzouk and Durandeau, 2004;Boursinos and Dimitriou, 2007;Lohmeyer et al, 2007). These latter cases in every way resemble the case reported herein.…”
Section: Scientific Clarificationmentioning
confidence: 99%
“…Nerve sheath ganglions occurring within the sheaths of the peripheral nerves have been reported in the literature as early as 1963, but they are relatively rare findings [2]. In the upper extremity, nerve sheath ganglions occur most commonly in the ulnar nerve, as it curves through the cubital tunnel [5,6,12,18]. Other reports in the median nerve, supraspinatus nerve and the posterior interosseous nerve were also noted [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nerve sheath ganglions are most commonly found in peroneal or tibial nerve in the lower limb [12,40] or ulnar nerve in the upper extremity [9,11]. This type of intramuscular ganglion is called an intramuscular cyst arising from the neurilemma.…”
Section: Intramuscular Cysts Arising From the Neurilemmamentioning
confidence: 99%
“…However, intramuscular cysts at the proximal calf are rare, and the etiologies of these cysts are diverse. Some case reports have shown that atypical Baker's cysts [3,4], cysts arising from the proximal tibiofibular joint (PTFJ) [5][6][7][8] and nerve sheath ganglions [9][10][11][12], can lead to intramuscular cysts at the proximal calf. The clinical presentation of these cysts is usually a painless mass along the calf.…”
Section: Introductionmentioning
confidence: 99%